2017
DOI: 10.1186/s12870-017-1057-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep Super-SAGE transcriptomic analysis of cold acclimation in lentil (Lens culinaris Medik.)

Abstract: BackgroundFrost is one of the main abiotic stresses limiting plant distribution and crop production. To cope with the stress, plants evolved adaptations known as cold acclimation or chilling tolerance to maximize frost tolerance. Cold acclimation is a progressive acquisition of freezing tolerance by plants subjected to low non-freezing temperatures which subsequently allows them to survive exposure to frost. Lentil is a cool season grain legume that is challenged by winter frost in some areas of its cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
(53 reference statements)
0
12
0
1
Order By: Relevance
“…Understanding of underlying molecular mechanism of heat tolerance is still unknown in lentil. However, some reports shedding light on molecular mechanisms of other abiotic stresses like drought and cold are available 7,70 . Transcriptome analysis may provide an overview of novel genes and regulatory networks linked with heat tolerance mechanism in lentil.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of underlying molecular mechanism of heat tolerance is still unknown in lentil. However, some reports shedding light on molecular mechanisms of other abiotic stresses like drought and cold are available 7,70 . Transcriptome analysis may provide an overview of novel genes and regulatory networks linked with heat tolerance mechanism in lentil.…”
Section: Discussionmentioning
confidence: 99%
“…LEAs, like PROTs, appear to bind preferentially to cytoplasmic facing membrane lipids, and stabilize these structures to prevent protein aggregation [20,24,36,37,38]. Little is known about the role of the adhesive/proline-rich proteins (APRPs) and low temperature inducible proteins (LTIs) in the cold stress response, however, both were found to accumulate in plants under cold stress, strongly suggesting that they have a protective function under these conditions [39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…LEAs preferentially bind to cytoplasmic facing membrane lipids to stabilize these structures and prevent protein aggregation (Bray, ; Cuming, ; Roberts, DeSimone, Lingle, & Dure III, ; Tolleter et al, ; Welin et al, ). Less is known about what role the adhesive/proline‐rich proteins ( APRPs ) and low temperature inducible proteins ( LTIs ) might play in the plant cold stress response; however, both are known to accumulate in plants under cold stress and several studies have suggested a protective function for APRPs and LTIs under these conditions (Barrios et al, ; Kawarazaki et al, ; Kim et al, ; Li et al, ; Recchia, Caldas, Beraldo, da Silva, & Tsai, ; Tseng, Hong, Yu, & Ho, ).…”
Section: Discussionmentioning
confidence: 99%
“…LEAs preferentially bind to cytoplasmic facing membrane lipids to stabilize these structures and prevent protein aggregation (Bray, 1993;Cuming, 1999;Roberts, DeSimone, Lingle, & Dure III, 1993;Tolleter et al, 2010;Welin et al, 1994). have suggested a protective function for APRPs and LTIs under these conditions (Barrios et al, 2017;Kawarazaki et al, 2013;Kim et al, 2004;Li et al, 2016;Recchia, Caldas, Beraldo, da Silva, & Tsai, 2013;Tseng, Hong, Yu, & Ho, 2013).…”
Section: Discussionmentioning
confidence: 99%